The profile and innovation outcomes of South African doctoral graduates in STEM, 2000–2018: A mixed methods study - Albertyn, Charl Hofmeyr (Stellenbosch : Stellenbosch University, 2023)
Thesis (DPhil)--Stellenbosch University, 2023.